Orientação para o mercado e fidelização de clientes: em estudo no setor bancário brasileiro - Amaral, Daniel (2011)
This dissertation aimed at exploring market orientation and customer loyalty in the Brazilian banking sector. The objective was to identify the association between them. A qualitative study with descriptive nature was made. The sample consisted of fifteen professionals in areas responsible for customer understanding, care and loyalty. The participating banks were Itaú, Bradesco, Caixa, Santander and Citibank. Data collection was conducted through interviews with a semi-structured guide and for the analyses, it was applied techniques of templates’ analyses. The results suggest that several points in the literature of market orientation were found in participants' reports, such as (1) the constant search for understanding and meeting the expressed needs of clients and (2) inter-functional coordination. On the other hand, some concepts were not constant, as (1) the search in the care of future needs and (2) the company's response, since banks do not react quickly assessed the competitive actions, due to bureaucracy, complexity and planning already determined. Regarding the identification of loyalty types, banks are in a constant structure to better meet the current customers needs. Thus, a large proportion of customers are actually loyal, proven by time of relation, number of services increase and recommendation. But there is still a large volume of customers that continues the relationship due to an inertial state, aggravated by the sight of commodity market. Thus, there are many opportunities for improvement, owing to needs expressed, whose solutions have not yet been reached. Moreover, banks are starting to develop processes that allow the detection of future needs. Mergers and acquisitions have impacted the industry in the loyalty of some customers groups, when there was a perceived drop in quality of services after the unification. Regarding the main objective, the analysis suggests that market orientation is associated with the loyalty, mainly in relation to structured processes for the company to have access to information, involving all areas to find solutions and take corrective actions. Despite the commodity market, some interviewees believe that the category is going through a maturing process in which the quest for customer loyalty will be even more important, since the inertia of the industry will not be as intense as today.